P99 Neonatal subdural haematoma following forceps-assisted delivery: a systematic review of the literature. Issue 3 (14th February 2019) - Zaben, M; Manivannan, S; Petralia, T; Leach, P
Abstract : Objectives: Subdural haematoma (SDH) is a recognised complication of forceps-assisted delivery (FAD). There are no guidelines regarding its management. This study aims to provide a better insight into the management and outcomes of neonatal SDH post FAD. Design: Retrospective review of our neonatal database and systematic review of the literature. Subjects: Neonatal cases presented with SDH after FAD. Methods: Retrospective database search of cases managed in our unit between January 20 111 and January 2018. Systematic review of the literature was performed using PRISMA guidelines. Inclusion criteria: (i) neonates, (ii) forceps-assisted delivery, (iii) evidence of SDH on imaging, with or without other traumatic lesions. Results: A literature search yielded 9 studies with 30 patients meeting our inclusion criteria, In addition three cases were identified from our institutional database. 42% (n=14) had their SDH managed surgically, with subsequent full neurological recovery in 57%. In comparison, 95% (n=18) of the conservatively managed patients made a full recovery. Hydrocephalus was present in 1 and 11 of the conservatively managed and surgically managed patients, respectively. Conclusions: Conservative management can lead to a full neurological recovery in SDH following FAD in neonates. However, a significant number may still need neurosurgical intervention for the SDH or subsequent hydrocephalus, therefore we advocate early transfer to a specialist neuroscience centre.